Influência do negro de fumo na absorção da radiação na região do infravermelho para o reaquecimento do copolímero de poli(tereftalato de etileno) - PET - Sofri, Fabio Lamon (Universidade Federal de São Carlos, 2005)
The objective of this work was to study the influence of the use of carbon black as infrared absorber to improve the PET resin heat-up during the stretching blow molding of bottles. It was investigated the correlation between the main physical properties of the carbon blacks and the source setup conditions and the PET infrared absorption. Therefore, five carbon blacks with different physical characteristics were selected and mixed with a PET resin bottle grade by injection molding. The correlation between particle size, surface area and structure of carbon black and the optical properties, rheological behavior and heat-up of the compositions were studied. The rheological measurements showed that the carbon blacks did not modify the profile of the PET rheological curve; however both the viscosity and elasticity properties of the PET were dependent on the carbon black particle size and structure. The differential scanning calorimetry (DSC) results showed that the carbon black particles modified the PET crystallization kinetics by increasing the induced crystallization temperature during the cooling step. Through the L* a* b* color measurements, it was verified that the L* color was indirectly proportional to the carbon black content. Finally, the heat-up performance was investigated using two methods: (a) the surface temperature measurement of samples heated under infrared lamps and, (b) the total absorption of each composition calculated using the spectrum data obtained by near infrared spectroscopy (NIRS). Using the scanning electron microscopy (SEM) it was verified that the carbon black content did not modify significantly the morphological aspect and the fracture surface of the compositions.
The influence of carbon black in the infrared absorption during the heating up of the polyethylene terephthalate
Keywords: Polímeros; Reologia; Processamento de polímeros; Reaquecimento; Moldagem por sopro; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS